SINTESIS NANOMATERIAL PERAK DENGAN KONTROL TERHADAP BENTUK DAN UKURAN - Admin APERTI (JURNAL TEKNOLOGIA, 2018)
Silver nanomaterials is widely investigated since its promising application for optics, catalysis, sensor, and anti-bacterial agent. The physical and chemical properties of nanomaterials are strongly dependent to its size and shape. Thus, it is important to be able to produce nanomaterials with define size and shape to better understand the most dominant factor influence its properties. Silver nanocubes with edge length of 50 nanometer is synthesized through polyol synthesis method using silver nitrate as the precursor. Seed-mediated growth technique is further utilized to synthesis silver nanocubes with larger edge length of about 200 nanometer. In conclusion, polyol method is a facile method to synthesize nanocubes with varieties of edge length.